STRATEGI EDUPRENEURSHIP MELALUI KONTEN KREATOR DALAM PEMANFAATAN PENGETAHUAN SEBAGAI PELUANG EKONOMI - Fristanti Yanuar Putri; Eka Shanti Aulia; Akbar Falaqul Mubarok; Diva Triani Oktaduama (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
The development of digital technology has created new economic opportunities through edupreneurship carried out by content creators. In this context, edupreneurship is not only focused on entertainment but also on the management and utilization of knowledge as an economic product. Recent data show that the global creator economy market value is projected to increase from USD 125.11 billion in 2024 to USD 160.91 billion in 2025, with a compound annual growth rate (CAGR) of 28.4%, and is expected to reach USD 436.71 billion by 2029. The purpose of this study is to examine edupreneurship strategies used by content creators in transforming knowledge into economic opportunities and to measure the effectiveness of its supporting factors. The research method applied is descriptive quantitative, by analyzing secondary data on market growth trends, economic value projections, and literature-based surveys. The results indicate that the most effective strategies include developing creative educational content, diversifying monetization models through digital courses and premium subscriptions, and collaborating with educational institutions and corporations. Quantitative analysis shows a positive correlation between the improvement of educational content quality and the growth of digital economic opportunities. In conclusion, content creators who consistently implement edupreneurship strategies can make a significant contribution to strengthening knowledge-based economies in the era of digital globalization.